A Review of Eating Disorders and Suicide Risk in Adolescence - Ida F. Dancyger; Victor M. Fornari (The Scientific World Journal)
This review examines the literature during the past 10 years about suicide risk and suicide during adolescence and young adulthood of individuals with eating disorders. Epidemiological surveys are summarized, including suicide rates, parasuicidal behaviors, associated risk factors, and comorbid psychopathology. Critical implications for the comprehensive assessment and treatment planning, including safety considerations, are discussed. Two clinical cases of women with long-standing eating disorders are described to highlight both the pragmatic considerations and the complex clinical challenges of working with patients with eating disorders who become suicidal. The potentially life-threatening issues of safety have not received sufficient attention, neither in the medical literature nor by the treating clinicians. All health care professionals who are treating patients with an eating disorder must be keenly aware of the serious risks of suicidal behavior and of suicide in this population.